Evaluation of fully covered self-expanding metal stents in benign biliary strictures and bile leaks - Lalezari, David (Baishideng Publishing Group Co., Limited, 2013)
AIM: To investigate the use of fully covered metal stents in benign biliary strictures (BBS) and bile leaks. METHODS: We studied 17 patients, at Harbor-UCLA Medical center (Los Angeles), with BBS (n = 12) and bile leaks (n = 5) from July 2007 to February 2012 that had received placement of fully covered self-expanding metal stents (FCSEMs). Fourteen patients had endoscopic placement of VIABIL(®) (Conmed, Utica, New York, United States) stents and three had Wallflex(®) (Boston Scientific, Mass) stents. FCSEMS were 8 mm or 10 mm in diameter and 4 cm to 10 cm in length. Patients were followed at regular intervals to evaluate for symptoms and liver function tests. FCSEMS were removed after 4 or more weeks. Resolution of BBS and leak was documented cholangiographically following stent removal. Stent patency can be defined as adequate bile and contrast flow from the stent and into the ampulla during endoscopic retrograde cholangiopancreatography (ERCP) without clinical signs and/or symptoms of biliary obstruction. Criterion for bile leak resolution at ERCP is defined as absence of contrast extravasation from the common bile duct, cystic duct remanent, or gall bladder fossa. Rate of complications such as migration, and in-stent occlusion were recorded. Failure of endoscopic therapy was defined as persistent biliary stenosis or continuous biliary leakage after 12 mo of stent placement. RESULTS: All 17 patients underwent successful FCSEMS placement and removal. Etiologies of BBS included: cholecystectomies (n = 8), cholelithiasis (n = 2), hepatic artery compression (n = 1), pancreatitis (n = 2), and Whipple procedure (n = 1). All bile leaks occurred following cholecystectomy. The anatomic location of BBS varied: distal common bile duct (n = 7), common hepatic duct (n = 1), hepaticojejunal anastomosis (n = 2), right intrahepatic duct (n = 1), and choledochoduodenal anastomatic junction (n = 1). All bile leaks were found to be at the cystic duct. Twelve of 17 patients had failed prior stent placement or exchange. Resolution of the biliary strictures and bile leaks was achieved in 16 of 17 patients (94%). The overall median stent time was 63 d (range 27-251 d). The median stent time for the BBS group and bile leak group was 62 ± 58 d (range 27-199 d) and 92 ± 81 d (range 48-251 d), respectively. All 17 patients underwent successful FCSEMS removal. Long term follow-up was obtained for a median of 575 d (range 28-1435 d). Complications occurred in 5 of 17 patients (29%) and included: migration (n = 2), stent clogging (n = 1), cholangitis (n = 1), and sepsis with hepatic abscess (n = 1). CONCLUSION: Placement of fully covered self-expanding metal stents may be used in the management of benign biliary strictures and bile leaks with a low rate of complications.